2014
DOI: 10.1007/s11547-014-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of skull base sutures and craniofacial anomalies in children with craniosynostosis: utility of multidetector CT

Abstract: High-resolution CT allows an accurate identification of both "major" and "minor" skull base suture synostosis and it represents the gold standard for the diagnosis of craniostenosis and for planning the proper surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
0
28
0
2
Order By: Relevance
“…However, the effective dose is used here for the purpose of comparison with other dosimetric studies and cannot be strictly considered as a measure of the stochastic radiation risk in children. Other studies for craniosynostosis CT have reported effective doses of 0.2-2.8 mSv [12,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 96%
“…However, the effective dose is used here for the purpose of comparison with other dosimetric studies and cannot be strictly considered as a measure of the stochastic radiation risk in children. Other studies for craniosynostosis CT have reported effective doses of 0.2-2.8 mSv [12,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 96%
“…However, another factor is the paucity of postnatal human developmental material investigated by histological methods. Human cranial arthrology has primarily been conducted using gross osteological (e.g., Cray Jr., Mooney, & Siegel, 2010; Krogman, 1930) or radiological (e.g., Calandrelli et al, 2014; Driessen et al, 2017; Kreiborg & Bjork, 1982; Rijkin et al, 2015) methods. Only rarely has basicranial material been studied histologically in humans (e.g., Melsen, 1974; Thilander & Ingervall, 1973) or nonhuman primates (e.g., Heinkele et al, 1989; Michejda, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 11 sites of articulation were examined (Figure 1, Table 1). Nomenclature for joints is based on the literature, with synonyms indicated (Baume, 1968; Balboni et al, 2005; Wealthall & Herring, 2006; Calandrelli et al, 2014; Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A CT scan may be unavoidable in complex (multisutural and syndromic types) or complicated types of craniosynostosis for treatment planning. The reported effective dose of radiation for a 3-D CT scan is in the range of 0.2 mSV to 2 mSV 3 5 8 22) . Recently, Ernst et al 7) reported that a 0.08 mSv 3-D CT protocol by using Model Based Iterative Reconstruction can be used in children with cranial deformities without compromising imaging quality.…”
Section: Discussion For Optimal Imaging For Diagnosis and Follow-up Omentioning
confidence: 99%